2016
DOI: 10.1108/arla-03-2016-0064
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance in family businesses from Latin America, Spain and Portugal

Abstract: Purpose The purpose of this paper is to summarize what is known about corporate governance in family firms from Ibero-American countries based on published research. Methodology The authors conducted a literature search to identify the articles that have been published about the corporate governance of family firms in Latin America, Spain, and Portugal between 1980 and 2014. The authors found 38 articles that provide the sample for this review. Findings The results indicate that research on governance in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Generally speaking, while Latin America "is the second most important emerging region in the world, after Southeast Asia, with an aggregated gross domestic product (GDP) roughly that of China's and three times larger than India's" and where families play a fundamental role in the business sector, relatively little family firm research concerning the region has been published (Vassolo et al, 2011). Additionally, research on family firm governance in Latin America lacks a systematic approach with a focus on a small number of countries (Cort es and Botero, 2016).…”
Section: Samplementioning
confidence: 99%
“…Generally speaking, while Latin America "is the second most important emerging region in the world, after Southeast Asia, with an aggregated gross domestic product (GDP) roughly that of China's and three times larger than India's" and where families play a fundamental role in the business sector, relatively little family firm research concerning the region has been published (Vassolo et al, 2011). Additionally, research on family firm governance in Latin America lacks a systematic approach with a focus on a small number of countries (Cort es and Botero, 2016).…”
Section: Samplementioning
confidence: 99%
“…The study illustrates that family governance is neglected not only by researchers as shown by Cortés and Botero (2016), but also by enterprises with advanced family life cycles. This despite the fact that, conflicts related to the family are those that produce the most destructive consequences for the family business (Ward, 2004;Dana and Smyrnios, 2010).…”
Section: Contributionmentioning
confidence: 89%
“…Concerning the leadership variable, centralized decision-making and the absence of mechanisms to guide and optimize operations lead to low profitability and the generation of a hostile work environment (Belausteguigoitia, 2012). Business alternatives are limited when new generations (Davis and Harveston, 1999;Woodfield and Husted, 2017), women (Keating and Little, 1997;Cortés and Botero, 2016) and external specialists (Briano and Poletti, 2017) are excluded from decision making. On the other hand, in an enterprise that lacks direction with defined roles and responsibilities (Kidwell et al, 2012) and performance monitoring and evaluation instruments (Vandebeek et al, 2016), there is also a lack of incentive to innovate and improve efficiency of operations in the different areas.…”
Section: Conflicts In Family Businessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vieira (2016) mentions that family businesses represent about 60 per cent of firms listed in the Portuguese capital market. Family firms may account for 80 to 85 per cent of the Portuguese firms, generating over 75 per cent of new jobs and contributing with over 70 per cent of the GDP (Cortés and Botero, 2016). The Portuguese setting, in which family firms constitute not only a significant proportion of listed firms, but also of the Portuguese firms in general, may lead to different results from those obtained in countries where the contribution of family firms to the economy is less important.…”
Section: Introductionmentioning
confidence: 98%